2015
DOI: 10.5194/nhess-15-2653-2015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a compound distribution based on weather pattern subsampling for extreme rainfall in Norway

Abstract: Abstract. Simulation methods for design flood analyses require estimates of extreme precipitation for simulating maximum discharges. This article evaluates the multi-exponential weather pattern (MEWP) model, a compound model based on weather pattern classification, seasonal splitting and exponential distributions, for its suitability for use in Norway. The MEWP model is the probabilistic rainfall model used in the SCHADEX method for extreme flood estimation. Regional scores of evaluation are used in a split sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 15 publications
1
33
0
1
Order By: Relevance
“…The EXP distribution is preferred for short periods since estimating the shape parameter is very uncertain. Blanchet et al (2015) found that GPD fails to robustly estimate the tail of the distribution because of a lack of data and unrealistic return levels for very long return periods (when the shape parameter is positive). An additional argument for the EXP model is that it is less affected by observational errors, which plays an important role here.…”
Section: Methodsmentioning
confidence: 99%
“…The EXP distribution is preferred for short periods since estimating the shape parameter is very uncertain. Blanchet et al (2015) found that GPD fails to robustly estimate the tail of the distribution because of a lack of data and unrealistic return levels for very long return periods (when the shape parameter is positive). An additional argument for the EXP model is that it is less affected by observational errors, which plays an important role here.…”
Section: Methodsmentioning
confidence: 99%
“…The scores relating the tail of the distribution have been proposed and used in Garavaglia et al (2011);Renard et al (2013); Blanchet et al (2015). In the split sample evaluation framework, four scores can be derived of a given score Sc: Sc (12) is the regional score when G , Sc (11) and Sc (22) are obtained symmetrically.…”
Section: Evaluation At Regional Scale In a Cross-validation Frameworkmentioning
confidence: 99%
“…Thus Blanchet et al (2015) proposed to base comparison on the divergence of the density of the ff (12) to the uniform density. A reasonable estimate of the latter is obtained by computing the 12) show mainly the three above alternatives: either a good fit (flat histogram), or a tendency towards a systematic under-or over-estimation (left-or right-skewed histograms).…”
Section: Evaluation At Regional Scale In a Cross-validation Frameworkmentioning
confidence: 99%
See 2 more Smart Citations